Mountaineers Are Always Free : Heritage, Dissent, and a West Virginia Icon - Hathaway, Rosemary V. (Book collections on Project MUSE., 2020)
"The West Virginia University Mountaineer isn't just a mascot: it's a symbol of West Virginia history and identity that's embraced throughout the state. Folklorist Rosemary Hathaway explores the figure's early history as a backwoods trickster, its deployment in emerging mass media, and finally its long and sometimes conflicted career-beginning officially in 1937-as the symbol of West Virginia University"--